MOTHER TONGUE-BASED MULTILINGUAL EDUCATION IMPLEMENTATION IN CEBU PHILIPPINES, IN THE EYES OF THE STAKEHOLDERS - Jennifer B. Gonzales, EdD (International Journal of Research Science and Management, 2018)
This study looked into the implementation of MTB-MLE in the DepEd Divisions of Cebu as how it is perceived, understood and experienced by the stakeholders. This phenomenological study is conducted in the school year 2016-2017. The data was collected through an interview of 14 stakeholders: School Heads in both private and public schools, teachers and parents. The results revealed that despite the mandated implementation of the MTB-MLE program, the stakeholders experienced and see flaws in the current MTB-MLE implementation, which made them kept their language ideologies making English as their preference to be taught since the first grade. It was recommended that proper training and selection of the teachers to handle the subject have to be done as well as the improvement of instructional materials to facilitate the class better. It was further recommended that College of Teacher Education in the Philippines will provide appropriate training to the preservice teachers to be effective at teaching MTB-MLE.